PROSES PEMBENTUKAN NILAI MORAL PESERTA DIDIK MELALUI PROGRAM KEGIATAN PEMBIASAAN KEAGAMAAN - Irna Rukmana; Damanhuri Damanhuri; Istinganatul Ngulwiyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this research is to find out the program of religious habituation activities carried out at SDN Serang 11 online, how teachers carry out religious habituation activities for the moral formation of students during the Covid-19 pandemic through online learning, and the results of the program of religious habituation on the formation of moral participants. students. The method used in this research is descriptive qualitative method. The data collection techniques used were observation, interview, and documentation techniques. The results of this study indicate that the process of forming moral values in students through online religious habituation activities has not been implemented optimally by teachers. So it can be concluded that the implementation of religious activities towards the formation of moral values of students that are carried out online at SDN Serang 11 is in the unfavorable category in the implementation process.